Development of Spin Game Media Assisted by Fun Teaching Method to Increase Students’ Learning Interest in Moral Faith Subjects - Wahyuddin, Sriwahyuni; Thaha, Hisban; Syam, Andi Achmad (Educational Journal of Learning Technology, 2026)
This study develops Fun Teaching–based Spin Game media to enhance students’ interest in learning moral beliefs at MTs Yaminas Noling, Luwu Regency. The research employed a Research and Development (R&D) design using the ASSURE model and involved 28 eighth-grade students. Media feasibility was assessed through validation questionnaires completed by media, material, and linguistics experts, as well as student interest questionnaires. Data were collected through observations, interviews, questionnaires, and documentation, and analysed using descriptive qualitative and quantitative techniques. Validation results showed that the media received a score of 85.4% (very valid), material validation reached 81.2% (very valid), and language validation obtained 75% (valid). Students’ learning-interest scores increased from 66.22% (good) before using the media to 95.61% (excellent) after its implementation. These findings indicate that the Fun Teaching–based Spin Game media is feasible and effective in increasing students’ learning interest.